Pemodelan Distribusi Nitrat di Kawasan Perairan Teluk Benoa - I Made Dharma Raharja; I Gede Hendrawan; Yulianto Suteja (Journal of Marine Research and Technology, 2018)
Benoa Bay is a highly regarded area by environmental conditions. Nitrate is important parameter for marine biota life. From previous research on nitrate contamination in Benoa Bay, the nitrate concentration has reached the standard condition of Bali Governor Regulation No. 16 of 2016 on Environmental Living Standard Quality and Living Standard Damage of 0,008 mg/L. Analysis previous researc still limited for surface water, so it is important to do more reasearch in water cloum of Benoa Bay. Research for nitrat constration can do whith observation data but the data observation need long time and many money. In this study using numerical modeling. The numerical modeler in this study is Finite Volume Coastal Ocean Model (FVCOM) which is modeled in 3-D. In the analysis of nitrate distribution in this study used the moemntum equations and advection-diffusion equations. From the model results for each condition the nitrate concentration at the surface of the Bay of Benoa is high in the western part of Benoa Bay and east of Benoa Bay. While in the water column of Benoa Bay the nitrate concentration tends to be influenced by the tidal elevation. The concentration nitrate is high in the low tide and the consectration nitrate is low in the high tide. The nitrate concentration from the surface to the bottom of the water have similar consentration.